A "happy ending" of mediastinal and abdominal lymphadenopathy associated with hepatosplenomegaly and pulmonary lesions. Issue 4 (25th February 2020) - Ben Salem, Fares; Triki, Wafa; Belkhir, Asma; Sbaihi, Siwar; Boukriba, Seif
Abstract: Major diagnosis for mediastinal and abdominal lymphadenopathy is lymphoma and tuberculosis. Spontaneous remarkable evolution should discuss viral infection on the condition that no corticosteroids have been taken before as they could magically improve an authentic lymphoma. Trial of antituberculosis treatment that is used in some cases could lead to a misdiagnosis as the viral‐infected patient can spontaneously heal as it is described in this case. Abstract : Major diagnosis for mediastinal and abdominal lymphadenopathy is lymphoma and tuberculosis. Spontaneous remarkable evolution should discuss viral infection on the condition that no corticosteroids have been taken before as they could magically improve an authentic lymphoma. Trial of antituberculosis treatment that is used in some cases could lead to a misdiagnosis as the viral‐infected patient can spontaneously heal as it is described in this case.